Sabbea gen. nov., a new diatom genus (Bacillariophyta) from continental Antarctica - Bishop, Jordan; Kopalová, Kateřina; Darling, Joshua P.; Schulte, Nicholas O.; Kohler, Tyler J.; Mcminn, Andrew; Spaulding, Sarah A.; Mcknight, Diane M.; van De Vijver, Bart (Phytotaxa, 2019)
The non-marine diatom flora of the Antarctic Continent includes several endemic taxa recorded over the past 100 years. One of these taxa, Navicula adminensis D.Roberts & McMinn, was described from the Vestfold Hills, East Antarctica. Detailed light and scanning electron microscopy observations have shown that based on its morphological features, the species does not belong to the genus Navicula sensu stricto. To determine the most closely related genera to N. adminensis, the morphological features of Adlafia, Kobayasiella, Envekadea, Stenoneis, Berkeleya, Climaconeis, and Parlibellus were compared with those of N. adminensis. Although each of these genera shows one or more similar features, none of them accommodates the salient morphological characteristics of N. adminensis. Therefore, a new genus, Sabbea gen. nov., is herein described, and Navicula adminensis is formally transferred to the new genus as Sabbea adminensis comb. nov. The genus Sabbea is characterized by uniseriate striae composed of small, rounded areolae occluded externally by individual hymenes, a rather simple raphe structure with straight, short proximal ends and short terminal raphe fissures, open girdle bands with double perforation and a very shallow mantle.